1983
DOI: 10.1111/j.2044-8341.1983.tb01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to a war environment and its effects on the blood pressure of pregnant women

Abstract: The present research examined the effects of living in an area which had been a target of terrorist activities for a long period, as well as the effects of war, on blood pressure of pregnant women. For this purpose, the blood pressures of 5804 Israeli pregnant women, who gave birth between July 1973 and June 1975 and who had lived in either high, medium or low military stress environments were compared. Blood pressures that were measured immediately before delivery were taken from the delivery record of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…While not found in all studies [100], evidence also supports a link between self-reported stressful life events and likelihood of preeclampsia [8]. Similar results were found using objectively determined stress; among 5,804 pregnant Isreali women living in a war environment, those classified as living in higher risk areas had higher blood pressure than women living in lower risk areas [101]. Null findings are also reported; among 3,679 nulliparous women in the Netherlands, neither work stress, anxiety, depression, nor pregnancy-related anxiety were associated with preeclampsia or gestational hypertension [102].…”
Section: Stress Reactivity and Maternal Healthmentioning
confidence: 69%
“…While not found in all studies [100], evidence also supports a link between self-reported stressful life events and likelihood of preeclampsia [8]. Similar results were found using objectively determined stress; among 5,804 pregnant Isreali women living in a war environment, those classified as living in higher risk areas had higher blood pressure than women living in lower risk areas [101]. Null findings are also reported; among 3,679 nulliparous women in the Netherlands, neither work stress, anxiety, depression, nor pregnancy-related anxiety were associated with preeclampsia or gestational hypertension [102].…”
Section: Stress Reactivity and Maternal Healthmentioning
confidence: 69%
“…Stress may contribute to the latter via promotion of preeclampsia (Arck, 2001; Hetzel et al, 1961; Kanayama et al, 1997; Khatun et al, 1999; Kurki et al, 2000; Landsbergis and Hatch, 1996; Rofe and Goldberg, 1983), a hypertensive disorder of pregnancy which is a leading cause of medically indicated preterm delivery. In animal models, pregnant rats exposed to cold stimulation of the paws for two weeks develop symptoms consistent with preeclampsia (Kanayama et al, 1997; Khatun et al, 1999), supporting a role for excessive stimulation of the sympathetic nervous system in the development of the disorder (Arck, 2001).…”
Section: Adverse Birth Outcomes In the United Statesmentioning
confidence: 99%
“…There have been descriptions of defined changes in relation to a specific diagnosis. One example is the incidence of pregnancy hypertension during war conditions, which has been shown to increase [23], Another is the increase in hypertension after migration [24]; a third cardiovascular deaths after be reavement [25]. and a fourth depression in relation to unemployment [26], Another kind of association that has been described is the one between life changes in general and dur ing illness.…”
Section: How Important Are Distressing Life Changes To Health?mentioning
confidence: 99%